Herbal Plant Classification Using EfficientNetV2B0 Model and CRISP-DM Approach - Sonita, Anisya; Anggriani, Kurnia; Vatresia, Arie; Putri, Tiara Eka; Darnita , Yulia; Zahra, Syakira Az; Aprilia, Vilda; Aziz, Dzakwan Ammar (Jurnal Teknik Informatika (Jutif), 2025)
Herbal remedies have long been utilized by Indonesian communities as part of traditional medicine. However, identification of these natural resources is often challenging due to the morphological similarities among various species, which demand expert knowledge to differentiate. This study aims to implement the EfficientNetV2B0 model architecture for classifying medicinal leaves through an Android-based application designed to support recognition tasks. The dataset was composed of augmented images of plant foliage. The model was trained using the TensorFlow framework and evaluated to measure classification performance. Results demonstrate that EfficientNetV2B0 achieves excellent accuracy, with validation scores exceeding 97%, outperforming several other deep learning models. The resulting application allows the general public to identify local medicinal species more easily. This study contributes to the field of computer vision by providing an accurate and efficient classification framework, particularly beneficial for health-related informatics in biodiversity-rich regions.